Characterizing Cumberland fluted biface morphology and technological organization. (April 2016) - Tune, Jesse W.
Abstract: Cumberland bifaces are frequently referenced in discussions of fluted point technology, Paleoindian chronologies, and Younger Dryas adaptations. However, due largely to the absence of stratified, datable components, limited information exists about Cumberland lithic technology. Only brief descriptions of morphology, reduction sequence, and potential chronologies based on exceptionally small datasets are available in the existing literature. To address these deficiencies, a study of biface morphology and technological organization was conducted based on over 900 fluted Cumberland bifaces. Morphological and technological similarities to other fluted biface types, as well as bracketing radiocarbon ages, suggest that Cumberland bifaces likely date to the early Younger Dryas. Cumberland appears to represent a maintainable technology used by people adapted to an environment with predictable resources. Reconstructing artifact life histories suggests Cumberland technology was related to a logistically mobile settlement strategy. Highlights: Cumberland technology has been poorly documented in comparison to other Paleoindian technologies. Over 900 Cumberland bifaces were analyzed in this study. Cumberland morphological and technological variability was characterized. A date range for Cumberland is estimated based on stratigraphic relationships and similarities to other biface types.